A Two-Way Road: Antagonistic Interaction Between Dual-Species Biofilms Formed by Candida albicans/Candida parapsilosis and Trichophyton rubrum - Garcia, Letícia Morais; Costa-Orlandi, Caroline Barcelos; Bila, Níura Madalena; Vaso, Carolina Orlando; Gonçalves, Larissa Naiara Carvalho; Fusco-Almeida, Ana Marisa; Mendes-Giannini, Maria José Soares (Frontiers in Microbiology, 2020)
Dermatomycoses include superficial fungal infections of the skin and its appendages. Trichophyton rubrum, Candida albicans, and Candida parapsilosis are some of the most prevalent species that cause dermatomycoses. Several studies show a variable predominance of Candida spp. in relation to dermatophytes, especially in onychomycosis and the possibility of isolating both from the same site. The ability of dermatophytes to form biofilms has recently been explored and there is currently no research demonstrating the involvement of these filamentous fungi in multi-species biofilms. Thus, this work aims to investigate the probable dual-species interaction between T. rubrum and C. albicans and T. rubrum and C. parapsilosis biofilms considering variable formation conditions, as well as the susceptibility of these dual-species biofilms against terbinafine and efinaconazole. Three conditions of formation of dual-species biofilms were tested: a) the suspensions of T. rubrum and Candida albicans or C. parapsilosis were placed together; b) suspensions of C. albicans and C. parapsilosis were added after pre-adhesion of T. rubrum biofilms and c) after maturation of T. rubrum sessile cells. In the first and second conditions tested, in general, the quantification of metabolic activities, biomass and polysaccharide materials of mixed biofilms tend to resemble Candida monospecies biofilms. In the third condition, the profiles were modified after the addition of Candida, suggesting that T. rubrum biofilms served as substrate for the development of Candida biofilms. Scanning electron microscopy apparently showed Candida predominance, however, numerous blastoconidia were noted, most evident in the conditions under which Candida was added after pre-adhesion and maturation of T. rubrum biofilms. Despite the predominance of Candida, the presence of T. rubrum appears to inhibit C. albicans filamentation and C. parapsilosis development, confirming an antagonistic interaction. The fungal burden assays performed when the biofilms were formed together confirmed Candida predominance, as well as susceptibility to antifungals. Further studies should be performed to identify the components of the Candida and T. rubrum biofilm supernatants responsible for inhibiting dermatophyte growth as well as C. albicans filamentation.